Sistem Ekonomi Islam dalam Al-Qur’an & Hadits - Maula Nasrifah (Fakultas Ekonomi dan Bisnis Islam, 2016)
Basically a lot of basic economic concepts developed by capitalists have been discussed both by Muslim economists, both based on the source of primary law or a solicitation on the ruler. Thought Muslims used as a reference in running capitalist economic policy. Likewise were studied by students of various groups of non-Muslims who came from Europe. In the era of Islamic scientific treasures are already very familiar with European thinkers who have done translationtranslation of scientific works into various languages of Muslim west. Islamic Economic System was born out of the efforts of Muslim economic thinker who studied neighbor many weaknesses that are owned by the capitalist and socialist systems. They thought that too many weaknesses in both systems. Although the purpose of the three systems together, the fatherly justice and public welfare, but in the capitalist and socialist economic system does not involve interests in the hereafter carry out its activities. Unlike the Islamic economic system which departs from the investment paradigm in the world will determine the results that will be obtained in the hereafter.